1996
DOI: 10.1111/j.1440-1681.1996.tb02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fish Oil Prevents the Development of Renal Damage in Salt‐loaded Stroke‐prone Spontaneously Hypertensive Rats

Abstract: 1. Stroke-prone spontaneously hypertensive rats (SHRSP) fed a high salt diet rapidly develop proteinuria, a marker of renal damage. We have recently shown that supplementing the diet of these rats with pure omega-3 fatty acids can inhibit the development of proteinuria. The aim of the present study was to examine the underlying renal pathology and to see whether a similar benefit could be obtained with fish oil or canola oil. 2. Diets containing sodium (2% by weight) and 5% fish oil, canola oil, olive oil or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(1 reference statement)
4
11
0
Order By: Relevance
“…This finding is similar to the reported effects of FO in SHRs (44,87). However, as with blood pressure, urine protein excretion in SS ϩ HSD ϩ FO rats remained significantly elevated compared with that of the SR ϩ HSD rats.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This finding is similar to the reported effects of FO in SHRs (44,87). However, as with blood pressure, urine protein excretion in SS ϩ HSD ϩ FO rats remained significantly elevated compared with that of the SR ϩ HSD rats.…”
Section: Discussionsupporting
confidence: 78%
“…In accord with several studies in SHRs (6,44,62,91), we demonstrate that FO prevents the development of chronic glomerular, tubulointerstitial, and vascular alterations in SS ϩ HSD rats. These extensive histopathological lesions were also observed in rats treated with HYD to lower blood pressure (SS ϩ HSD ϩ HYD).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The SHRSP rat model used in the present study is a widely used model for hemorrhagic stroke and essential hypertension (31)(32)(33). In this model, the FA composition of dietary fats had no major influence on the development of hemorrhagic stroke and life span of SHRSP rats, in contrast to models of cardiovascular diseases (21,22,(34)(35)(36). In humans also, a recent epidemiological study showed that the risk of developing hemorrhagic stroke is not associated with dietary levels of MUFA and PUFA (37).…”
Section: Discussionmentioning
confidence: 98%